Highly N2‐Regioselective TsOH‐Catalyzed Olefin Hydroamination: Metal‐Free Synthesis of N2‐Alkyl‐1, 2, 3‐triazoles. Issue 6 (21st March 2017) - Wei, Hao; Hu, Qingxia; Ma, Yutao; Wei, Liangming; Liu, Jiaqiang; Shi, Min; Wang, Feijun
Abstract: A highly N 2 ‐regioselective functionalization of 2 H ‐1, 2, 3‐triazole and 1 H ‐1, 2, 3‐triazole was achieved via a para ‐toluenesulfonic‐acid‐catalyzed olefin hydroamination. The reaction afforded the corresponding products with up to 92 % N 2 regioselectivity. Abstract : N1, N2, N123, go ! A highly N 2 ‐regioselective TsOH‐catalyzed olefin hydroamination using NH ‐ 1, 2, 3‐triazoles as the N‐nucleophilc reagents leading to N 2 ‐alkyl‐1, 2, 3‐triazoles is reported. The reaction showed good to excellent N 2 ‐selectivities.